2016
DOI: 10.1111/fmii.12069
|View full text |Cite
|
Sign up to set email alerts
|

Bank Diversification and Overall Financial Strength: International Evidence

Abstract: There are many studies in the finance and management literature that examine the impact of diversification on performance. Yet, the literature remains inconclusive as for the potential benefits in terms of risk and return. The present study aims to re‐examine this issue, while proposing a methodological framework that integrates various bank performance and risk indicators into a single measure of financial strength. Using an international sample of commercial banks, we find that diversification in terms of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 87 publications
(174 reference statements)
1
42
0
1
Order By: Relevance
“…Applying system GMM methodology, they concluded that diversification across and within both interest and non-interest income-generating activities decreases insolvency risk (increases stability). Doumpos et al (2016) also found a positive relationship between diversification and financial strength (stability). So, in our first hypothesis we will also expect a positive relationship between revenue diversification and bank stability.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 84%
See 1 more Smart Citation
“…Applying system GMM methodology, they concluded that diversification across and within both interest and non-interest income-generating activities decreases insolvency risk (increases stability). Doumpos et al (2016) also found a positive relationship between diversification and financial strength (stability). So, in our first hypothesis we will also expect a positive relationship between revenue diversification and bank stability.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 84%
“…Consequently, the share of non-interest income has significantly increased for the banks of this region; banks on average earned about 32% of their operating income from non-interest income sources over the sample period of our study. Doumpos et al (2016), using a worldwide sample, concluded that revenue diversification is more beneficial for banks working in developing countries as compared to banks in developed countries. This fact warrants an intense investigation into the topic for South Asian banks which has been largely ignored in existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…See a recent study from Doumpos et al. () who also enter income diversification when analyzing bank diversification.…”
mentioning
confidence: 99%
“…Consistent with Elsas et al (2010), Doumpos et al (2016) we use gross interest revenue so that the income diversitymeasure is not unduly distorted by the profitability of income related activities.The DIV index takes values between zero if the bank is fully specialized in a business area and 0.75 if the bank generates a mixture of incomes totallybalanced on the four sectors. Increasing DIV index shows that banks tend to the taller income diversification level to seek new income sources [15,16].…”
Section: Measures Of Diversificationmentioning
confidence: 99%
“…It takes values from −2.5 to 2.5, with higher scores corresponding to better outcomes. Most of them are standard control variables in the banking literature [16].…”
Section: Control Variablesmentioning
confidence: 99%